PENGARUH KOMPETENSI DAN QUALITY OF WORK LIFE TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI : Studi Kasus Pada Koperasi Pegawai Pos Indonesia - Muhamad Rafly Alfarizi (2022)
This study aims to determine the effect of competence and quality of work life on organizational citizenship behavior with organizational commitment as a mediating variable for employees in the Pos Indonesia Employee Cooperative. This research is a quantitative study with a sample of 35 employees of the Indonesian Post Employee Cooperative. This study uses the Structural Equation Model (SEM) and the data analysis process uses SmartPLS version 3.0 as a measurement tool. The test results obtained (1) there is an influence between competence on the behavior of organizational members, (2) there is an influence between the quality of work life on the behavior of organizational members, (3) there is an influence between competence on the behavior of organizational members and organizational commitment as a mediating variable, (4) there is an influence between the quality of work life on the behavior of organizational members with organizational commitment as a mediating variable, (5) there is an influence of organizational commitment on the behavior of organizational members.